Differential and Integral Calculus by Feliciano and Uy, Exercise 1.1, Problem 8

If f\left(x\right)=x^2+1, find \frac{f\left(x+h\right)-f\left(x\right)}{h},\:h\ne 0.

SOLUTION:

\frac{f\left(x+h\right)-f\left(x\right)}{h}=\frac{\left[\left(x+h\right)^2+1\right]-\left(x^2+1\right)\:}{h}

\frac{f\left(x+h\right)-f\left(x\right)}{h}=\frac{x^2+2xh+h^2+1-x^2-1}{h}

\frac{f\left(x+h\right)-f\left(x\right)}{h}=\frac{2xh+h^2}{h}

\frac{f\left(x+h\right)-f\left(x\right)}{h}=\frac{h\left(2x+h\right)}{h}

\frac{f\left(x+h\right)-f\left(x\right)}{h}=2x+h

 

Advertisements